Cancer mortality in the British rubber industry. Issue 3 (August 1982) - Parkes, H G; Veys, C A; Waterhouse, J A; Peters, A
Abstract : Although it is over 30 years since an excess of bladder cancer was first identified in British rubber workers, the fear has persisted that this hazard could still be affecting men working in the industry today. Furthermore, suspicions have also arisen that other and hitherto unsuspected excesses of cancer might be occurring. For these reasons 33 815 men, who first started work in the industry between 1 January 1946 and 31 December 1960, have been followed up to 31 December 1975 to ascertain the number of deaths attributable to malignant disease and to compare these with the expected number calculated from the published mortality rates applicable to the male population of England and Wales and Scotland. The findings confirm the absence of any excess mortality from bladder cancer among men entering the industry after 1 January 1951 (the presumed bladder carcinogens were withdrawn from production processes in July 1949), but they confirm also a statistically significant excess of both lung and stomach cancer mortality. A small excess of oesophageal cancer was also observed in both the tyre and general rubber goods manufacturing sectors. American reports of an excess of leukaemia among rubber workers receive only limited support from the present study, where a small numerical excess of deaths from leukaemia is not statistically significant. A special feature of the study is the adoption of an analytical method that permits taking into account the long latent period of induction of occupational cancer.